The Influence of Independence, Experience, Gender, and Internal Control Auditor's Understanding of Audit Judgment in the Big Four Public Accounting Firms in Indonesia - Andriana, Gisella; Setiawan, Amelia; Wirawan, Samuel; Djajadikerta, Hamfri (Jurnal Disrupsi Bisnis, 2023)
This study aims to examine and analyze the influence of independence, experience, gender, and understanding of internal control auditors on the audit judgment of the big four public accounting firms in Indonesia. The population of this study involved all auditors working in the big four public accounting firms in Indonesia and 60 respondents sample used in this study. The data collection technique used a questionnaire through Google Form. Data analysis techniques in this study employed the tests of data quality, classic assumption, and hypothesis testing using SPSS 26.0 software. The results of this study indicate that independence and experience have an influence on audit judgment, while there is no influence in gender and understanding of the auditor's internal control on audit judgment. In simultaneous testing, it is known that the independence, experience, gender, and understanding of the auditor's internal control influence the audit judgment.